The State and Social Movements: An non Deferrable Dialectic - Peña y Lillo E., Julio (2012)
This article analyzes the role of social movements in incorporating unprecedented concepts surrounding environmental protection and sumak kausay (good living) into the Ecuadorian constitution of 2008. It examines the existing tensions between social movements and the government, as well as the political challenges that have come about in attempting to achieve these new constitutional objectives.